Functionalized MWCNTs in improving the performance and biocompatibility of potential hemodialysis membranes. Issue 68 (4th July 2016) - Kaleekkal, Noel Jacob; Rana, Dipak; Mohan, D.
Abstract : Functionalized multi-walled carbon nanotube incorporated polyetherimide mixed matrix membranes for blood purification application. Abstract : The need to develop innovative types of hemodialysis membranes stems from the increasing incidence of renal failure and the abysmally low availability of healthy kidneys for transplantation. We aim to improve the efficiency and biocompatibility of hemodialysis membranes by the incorporation of functionalized multi-walled carbon nanotubes/polyvinyl pyrrolidone (f-MWCNTs/PVP) composites into the polyetherimide membrane matrix. The mixed matrix membranes (MMMs) were characterized by Fourier transform infrared spectroscopy, porosity, thermo-gravimetric analysis, etc. The change in cross-sectional and top surface morphology of the flat sheet mixed matrix membranes could be observed using scanning electron microscopy and atomic force microscopy. The improvement in the hydrophilicity was confirmed by the smaller water contact angle values observed. Membranes with higher concentration of the f-MWCNTs exhibited significant creatinine adsorption from model solutions in static conditions. These membranes when challenged with model protein solutions (albumin, globulin, and fibrinogen), displayed a significant depression in the quantity of proteins adsorbed, which is an indication of enhanced biocompatibility. Moreover, the membranes also prolonged blood coagulation time, suppressed attachment/activation of platelets and prevented hemolysis of the contacted red blood cells. The improvement of Chang Liver cell viability evidenced by formazan adsorption and the double cell staining technique is an indication of the cytocompatibility of these MMMs. Hollow fiber membranes of the same composition were prepared and potted into a module so as to create an effective surface area of 0.7 m 2 . The ultrafiltration coefficient, human serum albumin retention, was evaluated and found to be superior for these prepared membrane modules. These mixed matrix hollow fiber membranes demonstrated a greater removal of uremic toxins due to adsorption as well as diffusion. These membranes should be further investigated as potential blood purification systems.